Description of a new species of the genus Henricohahnia Breddin (Hemiptera: Heteroptera: Reduviidae: Harpactorinae) from China, with a key to Chinese species - Zhao, Ping; Wang, Jianyun; Cai, Wanzhi (Zootaxa, 2014)
Henricohahnia parva sp. nov. is described and illustrated based on the specimens collected from Yunnan Province of China. It represents the smallest-sized species of the genus Henricohahnia Breddin so far known. A key to the eight Chinese species of the genus is provided.